Search Rate and Functional Response of a Eusocial Insect (Oecophylla longinoda) in a Tanzanian Mango Orchard. (28th February 2015) - Fast, Thora Samsø; Axelsen, Jørgen Aagaard; Lynegaard, Gina Kier; Mwatawala, Maulid; Offenberg, Joachim
Abstract : Weaver ants, Oecophylla spp., are famous for being efficient biological control agents as they prey on a variety of insects, and they are capable of suppressing a large number of pest species. Here, the search rate and functional response of Oecophylla longinoda were investigated in a Tanzanian mango orchard using feeding experiments. This was done by following the removal of prey, which constituted the foundation for estimating the search rate by aid of the Nicholson-Bailey and Lotka-Volterra models. The overall mean search rate was3.2 × 10 - 4 and1.7 × 10 - 4 over 30 minutes, when calculating the search rate using the Nicholson-Bailey equation and the Lotka-Volterra equation (modified Holling equation), respectively. The functional response investigations showed a linear relationship between removed prey and available prey, suggesting type I functional response or, alternatively, the initial phase of type II functional response. The results presented here are probably the first attempt to identify the functional response type of a colony of living predatory eusocial insects.